STRATEGI PENANGANAN KAWASAN PERMUKIMAN KUMUH DI KECAMATAN PULOMERAK KOTA CILEGON - Romidhoni, Mukhammad (Jurnal Kebijakan Pembangunan Daerah, 2025)
Slum settlements remain a significant challenge in the development of coastal and industrial areas, including Pulomerak District, Cilegon City. Rapid population growth driven by urbanization and labor migration has exerted intense pressure on basic infrastructure and the availability of decent housing, leading to the emergence of twelve slum locations across three urban villages. This study aims to identify the actual conditions of these slum areas and formulate appropriate strategies for their improvement using a descriptive qualitative approach and SWOT analysis. Data were collected through document review, field observations, and in-depth interviews with residents and key stakeholders. The findings indicate that most slum areas suffer from inadequate housing conditions, poor sanitation and drainage Slum settlements in Cilegon City, particularly in Pulomerak District, are spread across 12 neighborhoods in three sub-districts and are categorized as light slums according to the Ministry of Public Works and Housing Regulation No. 14 of 2018. The main issues include uninhabitable housing conditions, poor sanitation and drainage, limited access to clean water, and inadequate waste and wastewater management systems. Social factors such as low human resource capacity, weak inter-agency coordination, and limited public awareness further exacerbate the situation. The WO (Weaknesses–Opportunities) strategy is identified as the most effective approach by leveraging external opportunities—such as national programs, corporate social responsibility (CSR), and collaboration with NGOs and universities—to address internal weaknesses. To ensure the success of this strategy, strengthening multi-stakeholder partnerships and encouraging active community participation are recommended.